Numerical Analysis on Sliding-Type Transverse Splicing Connection Applied in Widening Continuous Concrete Box-Girder Bridge - Wenqing Wu; Chong Cao; Yuqin Wu; Jiyang Liu; Dan Liu; Liang Chen; Zheng Liu (Buildings)
When traditional joint structures are used to widen multi-span continuous concrete box girder bridges, excessive lateral deformation often occurs at the girder ends, typically leading to the squeezing and cracking of seismic blocks by the girder webs. To address these technical challenges, this paper investigates a new type of slide-rail lateral joint structure that can create a longitudinal sliding effect between two bridge decks of the old and new bridge box girders, thereby effectively reducing the lateral deformation at the girder ends. First, this paper employs the finite element method to conduct a numerical analysis of a real-world bridge widening project, exploring the working mechanism and application feasibility of this novel connection method. The results show that, in the case study, if the traditional joint method is used, the lateral displacement at the girder ends can reach up to 40 mm after three years of widening. However, when the slide-rail joint structure is employed, the lateral displacement at the girder ends is limited to no more than 6 mm. This demonstrates that the new joint method can indeed effectively address the issue of excessive lateral deformation at the ends of the widened structure. Second, given that the slide-rail lateral joint structure is a relatively precise engineering structure, this paper examines the lateral load transfer mechanism under loads such as wheel loads and foundation settlement differences. It discusses the load-bearing characteristics of various components, including square steel pipes, lateral connection rebars, concrete flange plates, and embedded rebars. Finally, through a parameter sensitivity analysis, it is found that the torsional stiffness of the square steel pipes is a critical parameter for ensuring the load-bearing capacity of the structure. Therefore, it is recommended to set the wall thickness of the square steel pipes to 5 mm. Based on these research findings, this paper theoretically demonstrates that the new slide-rail lateral joint structure can effectively solve the technical challenges encountered during the lateral joint widening of multi-span long-span concrete continuous box girder bridges, providing a new solution for this field.